Signaling Competence in Elections - Takakazu Honryo (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We analyze how political candidates can signal their competence and show that polarization might be a way of doing this. For this purpose, we study a unidimensional Hotelling-Downs model of electoral competition in which a fraction of candidates have the ability to correctly observe a policy-relevant state of the world. We show that candidates tend to polarize, even in the absence of policy bias. This is because proposing an extreme platform has a competence signaling effect and has a strictly higher probability of winning than proposing a median platform. The degree of polarization depends on how uncertain is the state of the world.
urn:nbn:de:bvb:19-epub-17403-9
Keywords: 330